Interdiscursividade e multimodalidade na construção do sentido textual: o ensino do gênero mangá nas aulas de língua portuguesa. - Larissa Mendes Figueiredo Gomes (2015)
This thesis is situated in the search line Reading, writing and teaching Portuguese and aims to study the manga Barefoot Gen: the birth of Gen, green wheat, Keiji Nakazawa, in Portuguese language classes, investigating relevance of implementation in the classroom of the principles of Interdiscursivity and Multimodality in the construction of the meaning of the work cited. On the various aspects involved in the generation of textual meaning, we believe that these principles are key strategies for interaction between text, author and reader reading interactive assumption here undertaken. We base ourselves for the development of this work in the Grammar of Visual Design Kress and van Leeuwen (1996) and the concept of interdiscursivity in Maingueneau (2008). The methodology used in the corpus analysis consisted of contrast, quantitatively and qualitatively, the results of comprehension activities applied to two classes of 7th grade at a Lagoa Santa-MG municipal educational school, which made reading the above work but had purposely differentiated teaching-learning situations. We will base us on theories about the language of comics, from Ramos studies (2014) and Eisner (2010) and will focus on the studies of Luyten (2012) on Japanese comics. Will be adopted studies of Kress and van Leewen (1996) concerning multimodality and design Visual Grammar, and Hodge and Kress (1988) for the reasoning of Social Semiotics and its role in different language modes of representation for completeness semantics. The Visual Grammar will be addressed to the analysis of how the different compositional structures are used to produce senses through visual communication in this manga. Ultimately, it will be revisited the theoretical foundation of Maingueneau (2008) to the question of interdiscourse, given the constituent discursive networks interdiscursivity present in the work of Keiji Nakazawa, marked by divergent discursive formations each other in the discursive space of World War II. The results show that working with reading the manga genre in the Portuguese classes, based on theoretical principles that refer to the process of creation, construction of meaning and discursive relations are important for the construction of textual meaning.